Penerapan Canva pada Matakuliah Pengembangan Portofolio di ITB STIKOM BALI - Ni Wayan Setiasih (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The rapid development of digital technology has increased the demand for students to demonstrate their competencies through professional digital portfolios, particularly in Information Systems programs where analytical, design, and visual communication skills are essential. This study aims to analyze the effectiveness of using Canva as a digital portfolio development tool in the Portfolio Development course at ITB STIKOM Bali. The research employed a descriptive quantitative approach, using a four-point Likert-scale questionnaire distributed to 30 students enrolled in the course. The collected data were analyzed using descriptive statistics to measure students’ perceptions regarding ease of use, learning effectiveness, visual creativity, digital literacy, and learning motivation. The findings indicate that Canva is perceived as very easy to use due to its intuitive interface and accessible design features. Canva is also considered effective in helping students present system analysis results and project documentation in a more structured and visually appealing manner. Moreover, the use of Canva enhances students’ visual creativity and digital literacy skills while increasing their motivation and confidence in completing portfolio assignments. These results suggest that Canva functions not only as a design tool but also as an educational medium that supports the academic and professional competencies required in the digital era. Therefore, integrating Canva into project-based and visually oriented courses is strongly recommended to improve the quality of student learning outcomes.